Methods of electromagnetic monitoring of the earthquake source - M. G. Savin; I. I. Rokityanskiy (Геофизический журнал, 2011)
In accordance with mathematical experiment, partial impedances of heterogeneous flat wave turned out to be very sensitive to small changes of electro-conductivity in the source of earthquakes. It allows application of impedance changes in real time as a method of monitoring of electro-conductivity of the source during the period of earthquakes preparation.